AI Dialog: Utilization, Challenges, and Ethics in the Age of Artificial Intelligence - Riya Widayanti; Tatik Mariyanti (Pandawan Sejahtera Indonesia, 2023)
In this writing, we will delve into every aspect of the utilization, challenges, as well as ethical considerations in harnessing Artificial Intelligence (AI) Technology, with a focus on ChatGPT, an exceptional language model. AI technology has become an inseparable element in modern life, manifesting across various sectors such as business, healthcare, governance, and several others. The capabilities of AI are capable of driving data-driven decision-making, reducing the potential for human errors, and enhancing process efficiency. However, its impact is also not devoid of potential risks, including data security and the replacement of human roles. To ensure intelligent AI usage, it is imperative to uphold AI ethics, protect user information and privacy, strive to prevent discriminatory practices, and ensure system safety stability. The questions raised in this study revolve around the benefits and challenges of implementing ChatGPT, optimizing its use, and its role in the realm of education. The mission of this study is to unravel the benefits, challenges, as well as ethical considerations in the utilization of ChatGPT in the AI era, while ensuring responsible steps in its application.